Research on Marketing Strategy of Tea Wine Products of DJ Wine Industry - Wang, Wei (Asia Pacific Economic and Management Review, 2025)
In recent years, the liquor market has developed rapidly, consumers’ demand for Baijiu (Chinese liquor) has upgraded, and market competition has become increasingly fierce. Wine-making enterprises, especially small and medium-sized ones, are facing severe challenges and urgently need scientific development strategies. This paper takes the tea wine products of DJ Wine Industry Co., Ltd. as the research object. Through on-the-spot investigation, it deeply analyzes its development overview and marketing status, studies the opportunities and threats in the external environment, as well as the advantages and disadvantages of the enterprise itself, and finds problems such as vague positioning, inappropriate pricing, poor channels, and single promotion methods. The study uses STP theory to segment, select and accurately position the target market of tea wine products; with the help of 4P theory, it optimizes the marketing strategy from four aspects: product, price, channel and promotion. At the same time, combined with the macro and micro environment of the company, it systematically adjusts the marketing status and strategy. This research aims to tailor a scientific and comprehensive marketing plan for DJ Wine Industry’s tea wine products, helping it formulate a perfect marketing plan according to its actual situation, improve market competitiveness and share, and achieve sustainable development. The research results can not only provide reference for DJ Wine Industry, but also offer new ideas and methods for similar liquor enterprises to optimize marketing strategies, formulate sales plans, and promote the development of China’s liquor industry.